The Effect of Entrepreneurial Literacy and Self-Efficacy on Entrepreneurial Intention of Entrepreneurship Students at Univesitas Negeri Makassar - Fajriani Azis (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This study aims to determine the effect of entrepreneurial literacy and self-efficacy partially and simultaneously on entrepreneurial intentions in entrepreneurship students at Universitas Negeri Makassar. This research includes descriptive quantitative research with a population of 255 students. Determination of the sample using propionate stratified random sampling technique and obtained a sample of 72 students. Data were obtained through distributing questionnaires with a Likert scale. The analysis technique used is descriptive statistics and inferential statistics. The results showed that both partially and simultaneously, entrepreneurial literacy and self-efficacy have a positive and significant effect on entrepreneurial intention of entrepreneurship students at Universitas Negeri Makassar. The results of this study mean that the higher the entrepreneurial literacy and self-efficacy of students both partially and simultaneously will increase the entrepreneurial intention of entrepreneurship students of Universitas Negeri Makassar.